Mitochondrial-COII sequence polymorphism reflects spatial genetic clustering of Anopheles culicifacies sibling species E in Sri Lanka - Harischandra, I.N.; Dassanayake, R.S.; de Silva, B.G.D.N.K. (Journal of Vector Borne Diseases, 2021)
Background & objectives: Malaria infects around 216 million people annually with estimated 445,000 deaths globally. Anopheles culicifacies is the vector of malaria in Sri Lanka, a complex of five morphologically identical sibling species of which precise identification using DNA–based methods is still under experimentation. This study was carried out in Sri Lanka to observe the utility of BCE-PCR assay based on mitochondrial Cytochrome Oxidase II (COII) developed in India, in sibling species B and E identification in Sri Lanka, to characterize nucleotide and corresponding amino acid sequences of COII region in major vector sibling species E in Sri Lanka and to analyze the spatial distribution pattern of sibling species E in Sri Lanka using microsatellite markers. Methods: BCE-PCR was carried out for the samples to identify their sibling status. Sequencing of COII region was then carried out to investigate the genetic diversity of Sri Lankan sibling species E, sequences were aligned and compared; microsatellite genotyping was carried out and the spatial clustering pattern was analyzed. Results: Identification of sibling species B and E using BCE-PCR was confusing due to the heterogeneity in the COII region of sibling species in Sri Lanka. Non-synonymous substitutions were detected in COII gene amongst sibling species E. Spatial distributed two clusters were detected in the studied population. Interpretation & conclusion: Existence of genetic variants among sibling species is suggested in Sri Lanka. Further, the pattern of sibling species identification in BCE-PCR was reflected in the spatial clustering of sibling E in Sri Lanka.
Keywords: Anopheles culicifacies sibling E; COII; microsatellites; spatial clustering